Heat Shock Factor Is Involved in Regulating the Transcriptional Expression of Two Potential Hsps (AhHsp70 and AhsHsp21) and Its Role in Heat Shock Response of Agasicles hygrophila - Jin, Jisu; Li, Youzhi; Zhou, Zhongshi; Zhang, Hong; Guo, Jianying; Wan, Fanghao (Frontiers in Physiology, 2020)
Heat shock proteins are molecular chaperones that are involved in numerous normal cellular processes and stress responses, and heat shock factors are transcriptional activators of heat shock proteins. Heat shock factors and heat shock proteins are coordinated in various biological processes. The regulatory function of heat shock factors in the expression of genes encoding heat shock proteins (Hsps) has been documented in some model insects, however, the role of transcription factors in modulating Hsps in other insects is still limited. In this study, one heat shock factor gene (AhHsf) was isolated and its two potential target genes (AhHsp70 and AhsHsp21) were confirmed from Agasicles hygrophila. AhHsf sequence analysis indicated that it belongs to the Hsfs gene family. RT-qPCR showed that expression levels of heat shock factors and of two heat shock proteins significantly increased under heat stress. Injection with double-stranded Hsf RNA in freshly emerged adult beetles significantly inhibited expression of AhHsp70 and AhsHsp21, shortened the adult survival, drastically reduced egg production, and ultimately led to a decrease in fecundity. RNA interference (RNAi)-mediated suppression of AhHsp70 or AhsHsp21 expression also significantly affected expression of AhHsf. These findings reveal a potential transcriptional function of AhHsf to regulate expression of AhHsp70 and AhsHsp21, which may play a key role in A. hygrophila thermotolerance. Our results improve our understanding of the molecular mechanisms of the AhHsf - AhHsps signaling pathway in A. hygrophila.